Self-perceived body image, dissatisfaction with body weight and nutritional status of Brazilian adolescents: a nationwide study - Milene Moehlecke; Carina Andriatta Blume; Felipe Vogt Cureau; Christian Kieling; Beatriz D. Schaan (Elsevier, 2020)
Objectives: The purpose of this study was to evaluate the agreement and risk factors for underestimation and overestimation between nutritional status and self-perceived body image and to assess the prevalence and associated factors for dissatisfaction with body weight among Brazilian adolescents. Methods: Students aged 12-17 years participating in the Study of Cardiovascular Risk in Adolescents ("ERICA"), a multicenter, cross-sectional, school-based country-wide study, were included (n = 71,740). Variables assessed as covariates were sex, age, skin color, socioeconomic status, and common mental disorders (screened by the General Health Questionnaire, GHQ-12). Multinomial logistic regression was used to explore the association between covariates and combinations between self-perceived body image and body mass index (agreement, underestimation and overestimation). The associations between dissatisfaction with body weight and exposure variables were investigated using multivariable Poisson regression models. Results: Approximately 66% students rightly matched their body mass index with self-perceived weight (kappa coefficient was 0.38 for boys and 0.35 for girls). Agreement was higher among younger students and adolescents from low income households. Male sex, older age, and GHQ-12 score ≥3 were associated with weight overestimation. Prevalence of dissatisfaction with body weight was 45.0% (95% CI: 44.0-46.0), and higher among girls, older adolescents, those with underweight or overweight/obesity, as well as those who were physically inactive and with GHQ-12 ≥3. Conclusions: Most of the sample rightly self-perceived their body image according to body mass index. Students with body image misperception and those dissatisfied with their weight were more likely to present a positive screening for common mental disorders. Resumo: Objetivos: A finalidade deste estudo foi avaliar a concordância e os fatores de risco para subestimação e superestimação entre o estado nutricional e a autoimagem corporal e para avaliar a prevalência e os fatores associados à insatisfação com o peso corporal entre adolescentes brasileiros. Métodos: Foram incluídos estudantes entre 12 e 17 anos que participavam do Estudo de Riscos Cardiovasculares em Adolescentes ("ERICA"), um estudo multicêntrico, transversal, nacional e de base escolar (n = 71.740). As variáveis analisadas como covariáveis foram sexo, idade, cor da pele, situação socioeconômica e transtornos mentais comuns (triados pelo Questionário de Saúde Geral, QSG-12). A regressão logística multinomial foi usada para explorar a associação entre as covariáveis e as combinações entre a autoimagem corporal e o índice de massa corporal (concordância, subestimação e superestimação). As associações entre a insatisfação com o peso corporal e as variáveis de exposição foram investigadas com os modelos multivariáveis de regressão de Poisson. Resultados: Aproximadamente 66% dos estudantes associaram corretamente seu índice de massa corporal com o peso autopercebido (o coeficiente kappa foi 0,38 para meninos e 0,35 para meninas). A concordância foi maior entre jovens e adolescentes de baixa renda. Sexo masculino, adolescentes mais velhos e um escore QSG 12 ≥ 3 foram associados à superestimação do peso. A prevalência de insatisfação com o peso corporal foi 45,0% (IC de 95%: 44,0-46,0), maior entre meninas, adolescentes mais velhos, aqueles abaixo do peso ou com sobrepeso/obesidade, fisicamente inativos e com QSG-12 ≥3. Conclusões: A maior parte da amostra associou corretamente sua imagem corporal de acordo com o índice de massa corporal. Estudantes com distorção da autoimagem corporal e aqueles insatisfeitos com seu peso foram mais propensos a apresentar rastreamento positivo para transtornos mentais comuns. Keywords: Adolescents, Self-perceived body image, Body dissatisfaction, Body image perception, General Health Questionnaire, Mental health, Palavras-chave: Adolescentes, Auto-imagem corporal, Insatisfação com o corpo, Percepção da imagem corporal, Questionário de Saúde Geral, Saúde Mental